Probiotic Interventions in Systemic Sclerosis Patients: A Systematic Review and Future Prospects - Zahra Mirfeizi; Mahmoud Mahmoudi; Marzieh Monemi; Amin Tajerian; Arezoo Faridzadeh (Health Science Reports)
ABSTRACT Background and Aims Systemic sclerosis (SSc) is an uncommon autoimmune connective tissue disease distinguished by fibrosis and vascular abnormalities, often leading to gastrointestinal problems. This review explores the potential of probiotics in managing SSc‐related gastrointestinal issues and modulating immune responses, highlighting the need for innovative treatments to improve patient well‐being. Methods We performed an extensive literature search up to October 2023 in databases, including Web of Science, PubMed/MEDLINE, and Scopus. Result This review detected four articles that investigated the impact of probiotics on SSc. These studies, comprising non‐randomized observational studies and randomized clinical trials, provide preliminary insights suggesting that probiotics may be efficacious in modulating the immune response and, consequently, in improving gastrointestinal symptoms in SSc patients. Conclusion The comprehensive review suggests that probiotics may aid in managing gastrointestinal symptoms and modulating immune responses in SSc. However, it is essential to acknowledge the limited existing evidence, underscoring the need for more rigorous randomized controlled trials to thoroughly assess their effectiveness.